Acute effects of exercise on the inflammatory state in patients with idiopathic pulmonary arterial hypertension. Issue 1 (December 2016) - Harbaum, Lars; Renk, Emilia; Yousef, Sara; Glatzel, Antonia; Lüneburg, Nicole; Hennigs, Jan; Oqueka, Tim; Baumann, Hans; Atanackovic, Djordje; Grünig, Ekkehard; Böger, Rainer; Bokemeyer, Carsten; et al.
Abstract Background Exercise training positively influences exercise tolerance and functional capacity of patients with idiopathic pulmonary arterial hypertension (IPAH). However, the underlying mechanisms are unclear. We hypothesized that exercise modulates the activated inflammatory state found in IPAH patients. Methods Single cardiopulmonary exercise testing was performed in 16 IPAH patients and 10 healthy subjects. Phenotypic characterization of peripheral blood mononuclear cells and circulating cytokines were assessed before, directly after and 1 h after exercise. Results Before exercise testing, IPAH patients showed elevated Th2 lymphocytes, regulatory T lymphocytes, IL-6, and TNF-alpha, whilst Th1/Th17 lymphocytes and IL-4 were reduced. In IPAH patients but not in healthy subject, exercise caused an immediate relative decrease of Th17 lymphocytes and a sustained reduction of IL-1-beta and IL-6. The higher the decrease of IL-6 the higher was the peak oxygen consumption of IPAH patients. Conclusions Exercise seems to be safe from an immune and inflammatory point of view in IPAH patients. Our results demonstrate that exercise does not aggravate the inflammatory state and seems to elicit an immune-modulating effect in IPAH patients.